Latin American and Caribbean botanic gardens: Advances and challenges at national and regional levels - Faggi, Ana Maria (2012)
Background: The Association of Latin American and Caribbean Botanic Gardens (ALCJB) is a non-governmental organisation, dedicated to the investigation and conservation of plant diversity, and to the provision of outreach and education.Aims: The state of the art of the current conservation action of the ALCJB and its members are presented, and advances in achieving targets and further challenges are described.Results and conclusions: National Botanic Gardens (BGs) networks have played an important role in the conservation of national and regional biodiversity by consolidating existing gardens and supporting the creation of new ones, collaborating in the identification of flora, and in ex situ and in situ conservation. BGs promote education and implement mitigating actions at the ecosystem level to counter climate and land use change impacts on plant diversity. Such activities undertaken emphasise the new roles through which BGs can participate in conservation and promote sustainable ecosystem use. BGs have been implementing their action strategies based on a holistic vision of biodiversity that includes human activities and environmental changes. Motivated by significant progress of the national networks, the ALCJB has launched a new set of tasks to reach goals beyond the BGs integrating various dimensions of the environment.